Molecular epidemiology, pathogenicity, and structural analysis of haemoglobin variants in the Yunnan province population of Southwestern China - Zhang, Jie (Sci Rep, 2019)
Abnormal haemoglobin (Hb) variants result in the most commonly inherited disorders in humans worldwide. In this study, we investigated the molecular epidemiology characteristics of Hb variants, along with associated structural and functional predictions in the Yunnan province population of Southwestern China. A total of 41,933 subjects who sought haemoglobinopathy screening were included. Based on bioinformatics and structural analysis, as well as protein modeling, the pathogenesis and type of Hb genetic mutations were characterized. Among all individuals studied, 328 cases (0.78%) were confirmed as carriers of Hb variants, with 13 cases (0.03%) presenting α-globin variants, 313 (0.75%) β-globin variants, and two δ-globin variants. A total of 19 different mutations were identified, including three novel mutations. In addition, 48 cases of αα(CS) mutations and 14 cases of Hb H or Hb Bart’s were found. The isoelectric point, evolutionary conservation, and genotype-phenotype correlation for these mutations were predicted. Additionally, secondary and tertiary protein structure modeling were performed for three selected mutations. In conclusion, the prevalence of Hb variants in the Yunnan population is much higher than other regions of China. Complete characterization of these Hb variants is essential for generating a rational strategy to control the haemoglobinopathies in this region.